Bullying Prevention in Schools Through a Respect-Based CTL Learning Model - Deo Varas; Saliman Saliman; Anik Widiastuti (The Innovation of Social Studies Journal, 2025)
Bullying remains one of the most pressing and persistent issues in educational settings, often leading to serious psychological and social consequences for students, including anxiety, depression, and social withdrawal. Given its damaging and widespread impact, effective intervention strategies are urgently needed. This study explores the implementation of the Contextual Teaching and Learning (CTL) model integrated with a respect-based approach as a response to the bullying crisis in schools. Employing a quasi-experimental design with a pretest-posttest control group, data were collected through questionnaires administered to 70 students. Analysis using a t-test revealed a significant reduction in bullying behavior in the experimental group, with a Sig. (2-tailed) value of less than 0.001. The findings suggest that embedding respect-oriented values into the CTL framework fosters a more inclusive and empathetic classroom climate, which in turn helps prevent bullying. The study concludes that a respect-based CTL model is a promising educational strategy for addressing and mitigating bullying behavior among students.